(untitled) (Journal of the College of Basic Education, 2022)
Total alkaline phosphatase (ALP) was measured in two groups of breast cancer patients, group 1 consisted of 27 patients with axillary metastases, group 2 consists of 4 patients with liver metastases .In addition , a group of control subjects was included . The results showed that total serum ALP was especially increased in group 2. ALP was purified from sera of patients with breast cancer by gel filtration on a sepharose CL-6B(106+30)cm and high molecular weight alkaline phosphatase isoenzyme (HALP) was isolated at pH 7.4.